Association of Oral Candidiasis with Oral Lichen planus in patients using corticosteroid therapy- Meta-analysis - Alqahtani, Sulaiman S.; Faris M. Alabeedi (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
The Oral Lichen planus (OLP) is a chronic inflammatory disease that commonly affects the skin and mucous membranes. A difference of opinion among clinicians about whether oral lichen planus have been associated with oral Candidiasis. Nonetheless, in OLP patients, the oral candidiasis prevalence rate ranges from between 7.7% and 16.6%, as established through biopsy findings, whereas 37-50% has been noticed in culture findings. Oral Candidiasis has been linked to several local and systemic factors, including salivary gland dysfunction, dental prostheses, topical or inhaled corticosteroids, smoking, and the use of systemic medications. The Aim was to highlight the association of Candida in patients diagnosed with Oral Lichen planus (OLP), correlate the use of steroid therapy and enumerate the factors of using steroid therapy as implicated cause for oral Candidiasis. A search was made using search engines such as PubMed, Scopus, Cochrane database of systematic reviews, Science citation index, NIH Public access, and Clarivate analytics. The words using the research option for this field were "Oral Candidiasis" AND "Oral Lichen planus" or "Candidiasis" AND "Corticosteroids" or "Topical Corticosteroids" AND Oral Lichen planus or "Inhalation Corticosteroids" AND "Candidiasis" or "Oral Lichen planus" AND "Corticosteroids." The database search was made from 1991-2021. Additional articles were obtained regarding the literature of OLP and Oral Candidiasis, considered background material. The incidence of Oral Candidiasis and associated lichen planus following steroid therapy enlisted by various authors have been addressed. According to the results of this study, there is a positive correlation between the presence of oral Candidiasis in the oral lichen planus patients treated with corticosteroids.  In conclusion the meta-analysis concluded that there is a positive correlation between the presence of candida species in Oral Lichen Planus and steroid medication.